2012
DOI: 10.1165/rcmb.2011-0230oc
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Infected Alveolar Epithelial Cells Direct Neutrophil Chemotaxis and Inhibit Their Apoptosis

Abstract: The alveolar epithelium is a critical target for pulmonary viruses and can produce proinflammatory cytokines and chemokines upon viral infection. However, the molecular interactions between virus-infected alveolar epithelial cells and inflammatory cells, including polymorphonuclear leukocytes (PMNs), have not been thoroughly characterized. Rat coronavirus (RCoV) is used as a model to study the immune response to viral infection in the lung of the natural host. We have developed an in vitro model to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Alveolar epithelial cells have a key role in alerting the immune system to infection by respiratory viruses and shaping immune responses [37, 56, 57]. As viruses from several different families all target respiratory epithelial cells, it is important to understand the similarities and differences in how these cells respond to a diverse set of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar epithelial cells have a key role in alerting the immune system to infection by respiratory viruses and shaping immune responses [37, 56, 57]. As viruses from several different families all target respiratory epithelial cells, it is important to understand the similarities and differences in how these cells respond to a diverse set of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Primary rat alveolar epithelial cells cultured with distinct ATI and ATII phenotypes have been widely used as in vitro models for studies of lung physiology (Gonzalez et al, 2005;Qiao et al, 2003). Limitations of rat model systems include the very few genetic knock-out lines and established models of respiratory viral infections Miura et al, 2007;Rzepka et al, 2012). Based on the availability of well-characterized genetic lines and established models of respiratory viral pathogenesis, it is highly desirable to establish murine ATI and ATII cell models to study virus-host interactions in the differentiated cell types of the alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of respiratory viral infections is often correlated with an excessive inflammatory response in the lungs. Alveolar epithelial cells express proinflammatory cytokines and chemokines in response to viral infection and may be important in the initiation of these damaging inflammatory responses (Herold et al, 2006;Miura et al, 2007;Rzepka et al, 2012;Tate et al, 2011;Wang et al, 2011). In this study, we compared cytokine expression by murine ATI-like cells infected by MHV-1 or PR8, and IL-1␤ expression by ATI-like and ATII cells infected by MHV-1, PR8, or v2163.…”
Section: Discussionmentioning
confidence: 99%
“…The primary target of RCV in the alveoli is the type 1 alveolar epithelial cells (Funk et al, 2009;Miura et al, 2007). Using an in vitro model system, RCV infection induced proinflammatory cytokines and, specifically, CXC chemokines that inhibit polymorphonuclear leukocyte (PMN) apoptosis in type 1-like alveolar epithelia Rzepka et al, 2012). Furthermore, it was shown that RCV-infected rats deficient in PMNs have more severe and prolonged disease, indicating PMNs are required for an effective antiviral response but also contribute the lung pathology (Haick et al, 2014).…”
Section: Rat Coronavirus As a Model Of Respiratory Viral Infectionmentioning
confidence: 99%